DESAIN STRUKTUR DERMAGA PONTON DI PELABUHAN WAINGAPU, SUMBA TIMUR, NUSA TENGGARA TIMUR - Mahdi Karomalloh Swasana, Attar
Waingapu Port is a 3rd class port located in Nangamesi Bay, Waingapu, East Sumba Regency, East Nusa Tenggara Province. In its management, Waingapu Port is managed by PT. Pelabuhan Indonesia III (Persero). To increase productivity, PT. Pelabuhan Indonesia III (Persero) plans to develop a new wharf at this port. The problems that occur at this port are quite large differences in receding. From tidal data processing, it was found that the tidal mount value at Waingapu was 3.49 m, this is a strong reason to build a pontoon wharf at this port. In this final project, the author designed a pontoon wharf on the location of the planned new dock development. Pontoon jetty was chosen because it is suitable for areas with large tidal differences, so that this wharf can follow the tides that occur thus making it easier to mobilize people and goods to and from the ship. The structure of the pontoon has six degrees of freedom, but in the design of the pontoon wharf, the pontoon will be guided by piles at each end so that the ponton only has one degree of freedom in the form of heave. In addition, pontoon wharf can save the use of piles, so that if the soil bearing capacity is poor, the dock will still be able to operate. The discussion in this final project includes the processing of environmental data, determining pontoon wharf layout in general, the following design analysis of pontoon structure and gangway and design and analysis of the dynamics of the pile structure that serves as a barrier to keep the pontoon in place. In the analysis of pontoon and gangway structures will be modeled pontoon and gangway structures when influenced by vertical loads, while in the analysis of the pile structure, the structure of the pontoon and the pile will be modeled when affected by environmental loads. The output of this final project is a comparison between the value of the unity check ratio (UCR) as a result of manual analysis with the modeling and examination of the strength of the gangway structure, pontoons and piles, all of which meet the design requirements, so that the pontoon wharf is feasible.